GUIDANCE AND COUNSELLING SERVICES WITH PANCASILA VALUES INTERVENTION IN PREVENTING JUVENILE DELINQUENCY ACTION - Tresna Suhartoni; Syifa Jauhar Nafisah; Nada Fristy Yusri (Universitas Islam Negeri Mataram, 2025)
Juvenile delinquency (juvenile delinquency) is a social problem that concerns the community, encompassing various actions, such as driving without a license, fighting habits, teasing each other (bullying), graffiti at school, blackmail, stealing, arguing with teachers, never doing schoolwork, skipping school, even the worrying ones are drinking alcohol, drug abuse, motorcycle gangs and free sex. Adolescence generally begins around the age of 13 and ends around the age of 21. The method employed is quantitative research with a one-group pretest-posttest design, a form of quasi-experimental design that aims to measure the effectiveness of the intervention by comparing data before and after treatment within the same group. The study's results showed that the majority of data (71.71%) indicated that students had not previously participated in guidance and counselling services. All (87.94%) of the students understood the dangers of juvenile delinquency and how to prevent it after participating in guidance and counselling services with Pancasila values intervention. All (83%) of the students stated that they were satisfied, and a small portion (17%) stated that they were not satisfied with the guidance and counselling services, including the Pancasila values intervention, in preventing juvenile delinquency. Counsellors, in addition to providing Islamic religious treatment on the first principle of Pancasila, also provided narratives regarding criminal law regarding juvenile delinquency in order to increase legal awareness of students by knowing the threat of imprisonment and as a shock therapy to students, so that they can understand the dangers of juvenile delinquency, that they are closer to Allah SWT.